18F PET with flutemetamol for the early diagnosis of Alzheimer's disease dementia and other dementias in people with mild cognitive impairment (MCI) - Martínez, Gabriel (Cochrane Database Syst Rev, 2017)
BACKGROUND: (18)F‐flutemetamol uptake by brain tissue, measured by positron emission tomography (PET), is accepted by regulatory agencies like the Food and Drug Administration (FDA) and the European Medicine Agencies (EMA) for assessing amyloid load in people with dementia. Its added value is mainly demonstrated by excluding Alzheimer's pathology in an established dementia diagnosis. However, the National Institute on Aging and Alzheimer's Association (NIA‐AA) revised the diagnostic criteria for Alzheimer's disease and the confidence in the diagnosis of mild cognitive impairment (MCI) due to Alzheimer's disease may be increased when using some amyloid biomarkers tests like (18)F‐flutemetamol. These tests, added to the MCI core clinical criteria, might increase the diagnostic test accuracy (DTA) of a testing strategy. However, the DTA of (18)F‐flutemetamol to predict the progression from MCI to Alzheimer’s disease dementia (ADD) or other dementias has not yet been systematically evaluated. OBJECTIVES: To determine the DTA of the (18)F‐flutemetamol PET scan for detecting people with MCI at time of performing the test who will clinically progress to ADD, other forms of dementia (non‐ADD) or any form of dementia at follow‐up. SEARCH METHODS: The most recent search for this review was performed in May 2017. We searched MEDLINE (OvidSP), Embase (OvidSP), PsycINFO (OvidSP), BIOSIS Citation Index (Thomson Reuters Web of Science), Web of Science Core Collection, including the Science Citation Index (Thomson Reuters Web of Science) and the Conference Proceedings Citation Index (Thomson Reuters Web of Science), LILACS (BIREME), CINAHL (EBSCOhost), ClinicalTrials.gov (https://clinicaltrials.gov), and the World Health Organization International Clinical Trials Registry Platform (WHO ICTRP) (http://www.who.int/ictrp/search/en/). We also searched ALOIS, the Cochrane Dementia & Cognitive Improvement Group’s specialised register of dementia studies (http://www.medicine.ox.ac.uk/alois/). We checked the reference lists of any relevant studies and systematic reviews, and performed citation tracking using the Science Citation Index to identify any additional relevant studies. No language or date restrictions were applied to the electronic searches. SELECTION CRITERIA: We included studies that had prospectively defined cohorts with any accepted definition of MCI at time of performing the test and the use of (18)F‐flutemetamol scan to evaluate the DTA of the progression from MCI to ADD or other forms of dementia. In addition, we only selected studies that applied a reference standard for Alzheimer’s dementia diagnosis, for example, National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer’s Disease and Related Disorders Association (NINCDS‐ADRDA) or Diagnostic and Statistical Manual of Mental Disorders‐IV (DSM‐IV) criteria. DATA COLLECTION AND ANALYSIS: We screened all titles and abstracts identified in electronic‐database searches. Two review authors independently selected studies for inclusion and extracted data to create two‐by‐two tables, showing the binary test results cross‐classified with the binary reference standard. We used these data to calculate sensitivities, specificities, and their 95% confidence intervals. Two independent assessors performed quality assessment using the QUADAS‐2 tool plus some additional items to assess the methodological quality of the included studies. MAIN RESULTS: Progression from MCI to ADD was evaluated in 243 participants from two studies. The studies reported data on 19 participants with two years of follow‐up and on 224 participants with three years of follow‐up. Nine (47.4%) participants converted at two years follow‐up and 81 (36.2%) converted at three years of follow‐up. There were concerns about participant selection and sampling in both studies. The index test domain in one study was considered unclear and in the second study it was considered at low risk of bias. For the reference standard domain, one study was considered at low risk and the second study was considered to have an unclear risk of bias. Regarding the domains of flow and timing, both studies were considered at high risk of bias. MCI to ADD; Progression from MCI to ADD at two years of follow‐up had a sensitivity of 89% (95% CI 52 to 100) and a specificity of 80% (95% CI 44 to 97) by quantitative assessment by SUVR (n = 19, 1 study). Progression from MCI to ADD at three years of follow‐up had a sensitivity of 64% (95% CI 53 to 75) and a specificity of 69% (95% CI 60 to 76) by visual assessment (n = 224, 1 study). There was no information regarding the other two objectives in this systematic review (SR): progression from MCI to other forms of dementia and progression to any form of dementia at follow‐up. AUTHORS' CONCLUSIONS: Due to the varying sensitivity and specificity for predicting the progression from MCI to ADD and the limited data available, we cannot recommend routine use of (18)F‐flutemetamol in clinical practice. (18)F‐flutemetamol has high financial costs; therefore, clearly demonstrating its DTA and standardising the process of the (18)F‐flutemetamol modality is important prior to its wider use.